Facilities for investing in consols - Stanuell, Charles A. (Statistical and Social Inquiry Society of Ireland, 1912)
It is not my intention to go into the question of the National Debt as regards its origin; I propose to devote my time this evening to considering the manner in which dealings with the Consolidated Debt of Great Britain and Ireland are carried out, as regards purchase, payment of dividends, and sale.
Read December 6th, 1907
Keywords: Investment; National debt, Ireland; 314.15